1994
DOI: 10.1523/jneurosci.14-10-06084.1994
|View full text |Cite
|
Sign up to set email alerts
|

Efflux of dopamine from the synaptic cleft in the nucleus accumbens of the rat brain

Abstract: Synaptic release of dopamine in the nucleus accumbens of the intact rat brain elicited by a single electrical impulse applied to ascending dopaminergic fibers results in extracellular concentrations sufficient to bind the known dopamine receptors. The dopamine concentration observed after four rapid, sequential pulses is exactly four times greater and is unaffected by pharmacological antagonism of dopamine uptake and receptor sites at supramaximal concentrations. Thus, dopamine efflux from the synaptic cleft i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
353
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(388 citation statements)
references
References 67 publications
33
353
0
2
Order By: Relevance
“…Lesion and stimulation studies have shown that DA plays an important integrative role in motor performance, exploration, and cognition (Le Moal and Simon, 1991). Spatial and temporal signaling of DA neurotransmission is controlled by the plasma membrane DAT (Amara and Kuhar, 1993;Garris et al, 1994). In the present study, we have investigated behaviors in mice that have either one or both Dat1 alleles disrupted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lesion and stimulation studies have shown that DA plays an important integrative role in motor performance, exploration, and cognition (Le Moal and Simon, 1991). Spatial and temporal signaling of DA neurotransmission is controlled by the plasma membrane DAT (Amara and Kuhar, 1993;Garris et al, 1994). In the present study, we have investigated behaviors in mice that have either one or both Dat1 alleles disrupted.…”
Section: Discussionmentioning
confidence: 97%
“…Alterations in dopaminergic function have been associated with several different neurological and psychiatric conditions that include Parkinson's and Huntington's diseases, schizophrenia, Tourette's syndrome, attention deficithyperactivity disorder (ADHD), and substance abuse (Carlsson, 1987). A primary mechanism for regulating the concentrations of extracellular DA is through control of catecholamine reuptake by the DA transporter (DAT) (Amara and Kuhar, 1993;Garris et al, 1994). The distribution of the DAT within the mammalian CNS has been described and it is positively associated with the density of DA innervation (Scheffel et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The released DA can diffuse a few micrometers away from its release sites before being taken up by DA transporters (DAT) localized presynaptically outside of synaptic contacts [44]. The relatively slow dynamics of reuptake allows DA to invade the extrasynaptic space for a maximum of 12 μm [31,45] (Figure 2C), supplying a sustained, nearly homogenous, DA concentrations in the 10 nM range. This ambient concentration, which primarily acts on the D2 receptors in their high affinity state in the striatum [46], is believed to play an enabling role in movement, cognition, and motivation [47].…”
Section: Spine Da Receptors Mediate Extrasynaptic Transmissionmentioning
confidence: 99%
“…The action of DA in the synapse is terminated primarily by reuptake to the presynaptic membrane through the dopamine transporter (DAT) [6] . Otherwise, DA is partially removed by oxidation by monoamine oxidase orcatechol-O-methyltransferase in the synaptic cleft (Fig.…”
mentioning
confidence: 99%